The numbers of Canada Geese in Britain, 1976 - Ogilvie, M A (Wildfowl, 1977)
A census of the Canada Goose Branta canadensis in Britain was carried out in July 1976. The total has now reached about 19,400 compared with 10,500 in July 1968. The population is still divided into more or less discrete sub-populations and details are given of these. Complaints of agricultural damage were received from about one-quarter of all waters covered in the census. Control measures are reviewed.